Adenosine Concentration in Patients With Neurally Mediated Syncope - Groppelli, Antonella; Brignole, Michele; Chefrour, Mohamed; Gastaldi, Marguerite; El Oufir, Farid; Deharo, Jean Claude; Parati, Gianfranco; Guieu, Régis (Frontiers in Cardiovascular Medicine, 2022)
Background Either high or low values of adenosine blood level (ABL) can differentiate some forms of neurally mediated syncope (NMS). A rapid method of measurement has recently been developed. The aim of the present study was: (1) to compare ABLs in an unselected population of consecutive patients referred for evaluation of suspected NMS syncope and in healthy controls; and (2) to assess the relative prevalence of low and high adenosine forms among an unselected syncope population. Method Whole blood was collected after finger puncture, blood being deposit on a blot paper and adenosine concentration was measured by liquid chromatography/mass spectrometry (LC-MS/MS). Results Among 89 control subjects, the median ABL value was 0.54 μM (IQR, 0.46–0.65). The lowest 5% and the upper 95% percentile were 0.40 and 0.80 μM, respectively. Compared with healthy subjects, the 146 patients with syncope showed, on average, a higher median ABL value [0.63 (IQR 0.45–0.73, p = 0.04)] and a larger distribution of values. Low ABL values below the 5th percentile were observed in 28 (19%) patients, and, in five controls, p = 0.003 and high ABL values were observed in 26 (18%) patients and five controls, p = 0.009. Conclusions ABL is different in patients with suspected NMS than in healthy subjects. Patients with low and high adenosine values account for 19% and 18% of the general population. Thus, low and high ABL limits, as defined in this study, may help to define the purinergic profile of unselected subjects with a clinical diagnosis of suspected NMS.